The south Korean automobiles and spare parts export market - Beyrouti, Nouri (2010)
The relationship between the Lebanon and South Korea is a recent one, due to the remote geographical location of both countries with respect to each other. Lebanese knowledge of South Korea is limited relative to other countries in the Far East such as Japan and China; however, the bond is becoming stronger with time due to the efforts of both governments and the recognized booming economy of Korea. South Korea recognizes Lebanon as an experimental field for its products to be tested before offering them in the Middle Eastern Market. The main goods Lebanon imports from South Korea are automobiles and motor vehicles, car parts, electronics, plastics and others. Although the market share of the South Korean products is not that significant for the Koreans, a lot of opportunities are recognized for the future. South Korean brand names became so popular in the Lebanese market such as Samsung, LG, Kia, Daewoo and Hyundai. However quality is still associated with European, American and Japanese products. The purpose of this paper is to examine the importance of the Lebanese car market witch is characterized by its diversity, consumer preferences, and competitiveness in relation to South Korea automobiles brands and spare parts export market.